PDR brachytherapy with flexible implants for interstitial boost after breast-conserving surgery and external beam radiation therapy - Fritz, Peter; Berns, Christiane; Anton, Hans-Werner; Hensley, Frank W.; Assmann, Jörg; Flentje, Michael; Fournier, Dietrich von; Wannenmacher, Michael (Radiotherapy and oncology, 1997)
Background and purpose: For radiobiological reasons the new concept of pulsed dose rate (PDR) brachytherapy seems to be suitable to replace traditional CLDR brachytherapy with line sources. PDR brachytherapy using a stepping source seems to be particularly suitable for the interstitial boost of breast carcinoma after breast-conserving surgery and external beam irradiation since in these cases the exact adjustment of the active lengths is essential in order to prevent unwanted skin dose and consequential unfavorable cosmetic results. The purpose of this study was to assess the feasibility and morbidity of a PDR boost with flexible breast implants. Materials and methods: Sixty-five high risk patients were treated with an interstitial PDR boost. The criteria for an interstitial boost were positive margin or close margin, extensive intraductal component (EIC), intralymphatic extension, lobular carcinoma, T2 tumors and high nuclear grade (GIII). Dose calculation and specification were performed following the rules of the Paris system. The dose per pulse was 1 Gy. The pulse pauses were kept constant at 1 h. A geometrically optimized dose distribution was used for all patients. The treatment schedule was 50 Gy external beam to the whole breast and 20 Gy boost. PDR irradiations were carried out with a nominal 37 GBq 192-Ir source. Results: The median follow-up was 30 months (minimum 12 months, maximum 54 months). Sixty percent of the patients judged their cosmetic result as excellent, 27% judged it as good, 11% judged it as fair and 2% judged it as poor. Eighty-six percent of the patients had no radiogenous skin changes in the boost area. In 11% of patients minimal punctiform telangiectasia appeared at single puncture sites. In 3% (265) of patients planar telangiectasia appeared on the medial side of the implant. The rate of isolated local recurrences was 1.5%. In most cases geometrical volume optimization (GVO) yields improved dose distributions with respect to homogeneity and compensation of underdosage at the margins of the implant. Only in 9% of patients was the dose distribution impaired by GVO. However, GVO causes a number of substantial changes of the dose distribution which have consequences for its application. Conclusions: The interstitial CLDR boost of the breast can be replaced by the PDR technique without severe acute and late complications and without deterioration of the cosmetic results.